Uret Perusak Akar pada Rumput Halaman Kampus - Tri Harjaka; Edhi Martono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2010)
The study aims to identify of white grub attacking lawn in the park of campus of University of Gadjah Mada (UGM), Yogyakarta. Observations were conducted since July 2008 until January 2010. The results showed that Lepidiota stigma is a pest cause damage to the grass in the UGM park. The presence of beetles occurred in October of the same beginning of the rainy season. Flight and lay eggs period lasted from October 2009 until January 2010. First instar larvae of L. stigma began there in November and the third instar in the month of January 2010. Factors supporting the attack of L. stigma in the college environment is the availability of grass throughout the year, as the lights and the presence of trees as shelter for adult beetles.